Comparative analysis of asthma incidence between breastfed and bottle-fed children (aged 3-7 years old) - Roselyn M. Butalid; Laurence P. Alquiza; Charles D. P. Calderon; Earlgay S. L. Padilla (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
This study primarily aimed to compare the incidence of asthma between breastfed and bottle-fed children. And to determine if the demographic characteristics such as age, sex, ordinal position in the family and familial history of asthma affect the incidence of asthma as well. This study used Comparative-Survey Design through self-structured questionnaire given to the parents of the respondents who were the 3-7 year-old asthmatic children, selected through purposive sampling technique. The data gathered were thentabulated and analyzed using Chi-Square Method of Association. It was found out that most of the asthmatic respondents were between 5-7 years old which showed a high association between the age and the incidence of asthma. It implies that as the age increases, the incidence of asthma also increases. Results also showed that males are more likely to have high incidence of asthma than females. The incidence of asthma is likewise higher in eldest respondents than the middle or youngest. Moreover, there is a significant relationship between the familial history of asthma and its incidence. And finally, the feeding status of the respondents whether breastfed or bottle-fed during the first 6 months of life affects the incidence of asthma as the incidence is higher in bottle-fed than in breastfed respondents